Crossbreeding between Clearfield® rice varieties with local weedy rice in Malaysia - Anuar, Nur Hidayatul Shuhada (2017)
The introduction of imidazolinone-resistant Clearfield® varieties has successfully control weedy rice infestations. However, there is concern about the possibility of gene introgression from Clearfield® rice to weedy Oryza species which is likely to take place as the incidence of natural hybridization. This could produce herbicide resistant weedy rice and thus render the controlling of weedy rice with imidazolinone herbicide ineffective. The main objective of this study was to examine whether the gene introgression from Clearfield® varieties to local weedy biotypes can occur. The study was conducted in three stages. In the first study, Clearfield® rice varieties (CL1, CL2) and four local weedy rice biotypes (WR1, WR2, WR3, WR4) were grown in a pot inside the glasshouse to evaluate the differences in the vegetative and reproductive development of local weedy rice biotypes in comparison with Clearfield® varieties. In the second study, manual pollination between two Clearfield® rice variants and four local weedy rice biotypes were performed to investigate the response of crossed F1 progenies on imidazolinone herbicide. Crossed seeds were collected and germinated in trays before the progenies were sprayed with imidazolinone herbicide (OnDuty®) at day fourteen with a rate of 214 g/ha. The third study was done to confirm whether the gene introgression has occurred in the F1 progenies using ten different Simple Sequence Repeats (SSR) primer. From the first study, both CL varieties were proved to have a high percentage of germination rate at 80% and 65% for CL1 and CL2 respectively. Three out of four of weedy biotypes have a moderate percentage of germination rate ranged from 30 to 60% while WR4 has the lowest percentage of germination rate which was only 5%. All weedy biotypes were significantly taller than Clearfield® varieties. However, no significant differences in number of tillers were observed between them except for WR4 at sixty days after seeding (DAS). All weedy biotypes flowered ten to twenty days later than the Clearfield® varieties. In the second study, WR4 crossed with CL1 produced the highest number of fertile seeds, while the lowest number is from the crossing of WR4 with CL2. Clearfield® rice parent has high resistant towards Onduty® while the WR parent is highly susceptible to Onduty® with 70% of the seedlings were shown having severe injury after 1 week of application with herbicide. Progenies of WR crossed with CL2 showed less herbicide injury compared to the progenies of WR crossed with CL1. The results also showed that between CL1 and CL2 variants, CL2 has higher compatibility to cross with all WR biotypes, with 100% were successfully survived. In the third study, it showed that SSR primer RM251 is the suitable primer to confirm the hybridization between Malaysian Clearfield® rice and weedy biotypes. As a conclusion, gene introgression from Clearfield® varieties to weedy biotypes can occur. Flowering synchronization and genetic compatibility between Clearfield® varieties and weedy biotypes can influence the rate of gene introgression.